Acculturation to the global consumer culture: Ten years after and agenda for the next decade. Issue 3 (3rd July 2018) - Cleveland, Mark
Abstract: Globalization is shaping culture, modifying value systems, affecting social identities, and ultimately, altering the dispositions and behaviors of consumers worldwide. With more than 400 citations to date, Cleveland and Laroche's (2007) publication, which applied social identity and acculturation theories to the study of global consumer culture (GCC), is recognized as one of the defining works on the subject of marketplace globalization. Beyond the theoretical contributions, this research provided, for the first time, a multidimensional scale for measuring how individuals acquire and become a part of the emerging GCC (acculturation to the GCC, or AGCC). This paper (1) reviews the debates surrounding the effects of globalization on consumer behavior, (2) summarizes the extant applications of the AGCC framework and its constituents across numerous settings, and (3) outlines an agenda for future research on GCC.